IMPLEMENTASI PELAYANAN RAMAH ANAK MELALUI TEKNIK DISTRAKSI AUDIOVISUAL BAGI TENAGA KESEHATAN DI FASILITAS PELAYANAN KESEHATAN - Desty Lismayanti; Yanti Rosmiyanti; Sumitro Sumitro; Sarini Sarini; Okti Rahayu Asih; Difa Nur Fadillah (Bajang Institute, 2025)
Child-friendly healthcare services are essential to ensuring that children receive safe, comfortable, and psychologically supportive care during medical procedures. One of the most common causes of anxiety among preschool children is invasive procedures, particularly injections, which often result in fear, pain, and uncooperative behavior. Audiovisual distraction is a non-pharmacological intervention that has been shown to effectively reduce procedural anxiety and improve children's cooperation during clinical care. This community service program aimed to enhance the knowledge and practical skills of healthcare professionals in implementing audiovisual distraction techniques as part of child-friendly healthcare services in healthcare facilities. The program adopted a Participatory Learning and Action (PLA) approach involving 30 healthcare professionals, including nurses and midwives, through educational sessions, demonstrations, simulations, hands-on practice, and mentoring. Program evaluation was conducted using pretest–posttest assessments and observation checklists to measure participants' knowledge and competency in applying audiovisual distraction during pediatric procedures. The results demonstrated a significant improvement in participants' understanding of child-friendly care principles and their ability to integrate audiovisual distraction techniques into routine clinical practice. Healthcare professionals became more competent in selecting age-appropriate audiovisual media, establishing therapeutic communication with children and their caregivers, and creating a more supportive and less stressful clinical environment. Furthermore, the implementation of this program contributed to strengthening child-centered care practices by promoting positive healthcare experiences and reducing procedural anxiety among pediatric patients. This community empowerment initiative indicates that audiovisual distraction training is a practical, cost-effective, and sustainable strategy for improving the quality of pediatric healthcare services. Integrating this intervention into standard operating procedures is expected to enhance service quality, increase patient and family satisfaction, and support the development of child-friendly healthcare facilities